Depot-specific metabolic and inflammatory profiles in perirenal and renal sinus adipose tissue - Maria J. Pereira; Argyri Mathioudaki; Susanne Hetty; Amir Sedigh; Jan W. Eriksson; Maria K. Svensson (Molecular Medicine)
Abstract Background Alterations in kidney-associated adipose tissue depots, specifically renal sinus (RSAT) and perirenal adipose tissue (PRAT), may contribute to metabolic, cardiovascular, and chronic kidney diseases. We compared transcriptomic profiles and phenotypes, including adipocyte size, glucose uptake, and insulin action in RSAT and PRAT from healthy individuals. Methods Subcutaneous (SAT), omental (OAT) and renal adipose tissue biopsies were collected from healthy kidney donors (20 women, 20 men; BMI 20 to 36 kg/m2). Adipocyte size and basal and insulin-stimulated glucose uptake rate were measured in isolated adipocytes. Transcriptomic profiling and immune cell composition estimates (RNA seq, n = 30), were performed to evaluate differences between PRAT and RSAT, with OAT as a benchmark. Results PRAT exhibited significantly larger adipocytes and higher insulin-stimulated glucose uptake than RSAT. Of 1113 significantly differentially expressed genes (DEGs) (PRAT: 571 down- and 542 upregulated), thermogenic and metabolic genes (UCP1, CIDEA, and CKMT1B) were enriched in PRAT, while inflammation-related genes (NFKBIA, BIRC3, and IRF1) in RSAT. Pathway analysis indicated activation of metabolic pathways (TCA cycle and oxidative phosphorylation), in PRAT, which contrasts with the immune and inflammatory pathways in RSAT and OAT. Immune cell gene signatures revealed an anti-inflammatory environment in PRAT (eosinophils and activated NK cells), and a pro-inflammatory profile in RSAT (M0 macrophages). Immunohistochemistry confirmed higher CD68- and IL1B-positive cells in RSAT than in PRAT. When overweight individuals were compared to lean, genes related to the VEGF signaling were upregulated in PRAT and Ras signaling in RSAT. Additionally, metabolic pathways linked to the TCA cycle as well as carbon and fatty acid metabolism were downregulated. Conclusions The different kidney-associated adipose tissue depots exhibit distinct gene expression and functional profiles. PRAT displays higher expression of thermogenic markers and less inflammatory profile compared to RSAT and also OAT. In contrast, RSAT exhibits an inflammatory and macrophage-enriched profile, more closely resembling OAT. This study highlights the heterogeneity of the kidney-associated adipose tissue depots and could suggest that an excessive amount of RSAT may impact development of metabolic, cardiovascular, and chronic kidney diseases.